Relativistic intraction of laser pulse with thermal electron plasma - J, Vanchinkhuu (Scientific transaction of the National University of Mongolia. Physics, 2022)
The interaction of a short laser pulse (λp~L) with thermal fluid plasma in relativistic case is investigated in hydrodynamical approach. The one dimensional description of this process is developed and the fundamental equations describing the plasma quantities during the interaction are obtained. The wake generation by laser pulse is, also, investigated and the laser wake field in thermal plasma by a laser pulse is handled numerically. In weakly relativistic case, the wake potential propagating in snoidal wave form is obtained. While the wavelength of laser pulse is increased, the wavelength of plasma potential wave in thermal plasma is decreased compared to that in cold plasma. Also, due to the thermal motion, the amplitude of plasma wave is decreased.